2016
DOI: 10.1002/jhet.2236
|View full text |Cite
|
Sign up to set email alerts
|

Tetracyanoethene and 1‐Amino‐1,2,2‐ethenetricarbonitrile in the Synthesis of Heterocycles of Prospective Antioxidant and Antibacterial

Abstract: Reaction of 1,1,2,2‐ethenetetracarbonitrile (TCNE) with aroyl thioureas in dioxane catalyzed by few drops of piperidine, led to the corresponding 1,2,4‐oxathiazoles. Under the same reaction condition, thiosemicarbazide or thiosemicarbazone reacted with either TCNE or 1‐amino‐1,2,2‐ethene‐tricarbonitrile. The structures of the products were elucidated via NMR, IR, mass spectra, and elemental analyses. The mechanism of formation was discussed. Biological (against Gram‐positive and Gram‐negative bacteria) and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Recently Aly et al revealed the reaction pathway to 1,2,4-oxathiazoles employing the 1,1,2,2-ethenetetracarbonitrile (TCNE) reagent to heterocyclize aroyl thiourea precursors in dioxane (Scheme 7). Biological and antioxidant activities of newly synthesized heterocyclic cores were screened and SAR studies were inspected [38]. The proposed reaction pathway is shown in Scheme 8.…”
Section: Heterocyclization Reactionsmentioning
confidence: 99%
“…Recently Aly et al revealed the reaction pathway to 1,2,4-oxathiazoles employing the 1,1,2,2-ethenetetracarbonitrile (TCNE) reagent to heterocyclize aroyl thiourea precursors in dioxane (Scheme 7). Biological and antioxidant activities of newly synthesized heterocyclic cores were screened and SAR studies were inspected [38]. The proposed reaction pathway is shown in Scheme 8.…”
Section: Heterocyclization Reactionsmentioning
confidence: 99%
“…However, such a basic catalyst could also create a carboxylate anion from either chloroacetic acid or the pre-formed thiourea-chloroacetic acid. As a consequence, both the rate of amine–carboxylic acid interaction and reaction yield were remarkably reduced . Interestingly, compound 3 could be also obtained in excellent yield by utilizing ethyl bromoacetate instead of chloroacetic acid (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, both the rate of amine−carboxylic acid interaction and reaction yield were remarkably reduced. 45 Interestingly, compound 3 could be also obtained in excellent yield by utilizing ethyl bromoacetate instead of chloroacetic acid (Scheme 2). In addition, the stereoselective generation of the (Z)-stereoisomer could be explained depending on the allylic strain, as displayed in Figure 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Dicyano‐5‐amino‐2,5‐dihydro‐1 H ‐pyrazole‐1‐carbothioamide ( 89a ) was synthetized in 82% yield via interaction between 2 and 1,1,2,2‐tetracyanoethylene (TCNE, 88 ) in 1,4‐dioxane in the presence of a few drops of pyridine under reflux for 6 h (Scheme ) .…”
Section: Thiosemicarbazidesmentioning
confidence: 99%